Telecom reform : principles, policies and regulatory practices - Melody, William H. ed. (Technical University of Denmark LyngbyDK, 1997)
Addresses the telecom policy and regulatory reform process now in its formative stage. Examines the technological and economic trends, as well as policy and regulatory developments, to present and critique the principles, policies and practices associated with telecom reform.